A new approach to produce calcium-phosphate coatings on titanium; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Golovanova О. А. (Technologies and equipment for their implementation, 2017)
Title screen